Green Brand Characteristics For The Entrepreneurs - Haris, Risma (UNM Environmental Journals, 2017)
The environmental damage caused by the business world has been going on for decades.Environmental awareness has become an important issue for entrepreneurs. Green brandscale as a form of identifier (physical evidence) and differentiator (differentiator) for aproduct that is committed to the environment. The purpose of this study to identify thecharacter of the green brand on entrepreneurs in the city of Makassar. This study usedsurvey, resource as many as six young business actors with various products / services.research data is processed qualitatively descriptive. The results of the research obtainedcan be concluded that community awareness of the environment causes the product withthe green brand identity has effectively increased the attractiveness of the prospectiveconsumers who have a high concern for the environment, and with the green brand,business actors are aware that their products are a means to provide environmentaleducation to potential customers.